2008
DOI: 10.2478/fhort-2013-0102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rootstock on the growth and yielding of ‘Regina’ cherry trees

Abstract: The studies conducted in the years 2004 -2006 in a production orchard in the habitat conditions of the Wyżyna Sandomierska showed that the trees budded on Mazzard seedling grew more strongly than on Colt rootstock. No significant differences were observed between the rootstocks as for the trunk thickness and the crown size of young trees planted in 2001. In the group of trees planted in 1996, which were in the period of full fruiting, the crowns of trees budded on Mazzard seedling were significantly bigger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
2
5
0
2
Order By: Relevance
“…Sunburst, increased. These data are in accordance with the results of Moreno et al (2001) and Wociór (2008) who reported that on average, sweet cherry started to produce two years after planting and production increased in the 3 rd and 4 th years. In other studies, cherry started to produce between the 3 rd and 6 th year (Godini et al 2008).…”
Section: Tree Vigour and Yield Performancesupporting
confidence: 82%
“…Sunburst, increased. These data are in accordance with the results of Moreno et al (2001) and Wociór (2008) who reported that on average, sweet cherry started to produce two years after planting and production increased in the 3 rd and 4 th years. In other studies, cherry started to produce between the 3 rd and 6 th year (Godini et al 2008).…”
Section: Tree Vigour and Yield Performancesupporting
confidence: 82%
“…The discussed studies proved that after harvest the fruit exhibited better quality parameters-i.e., firmness and SSC-in the second year. Rootstocks can have different effects on the cultivars of sweet cherries grafted on them under different climatic and soil conditions (Hilsendegen 2004;Wociór 2008;Cantin et al 2010) and can modify a wide range of fruit quality parameters (Gonçalves et al 2005;Lugli and Sansavini 2008;Rozpara 2008;Kankaya et al 2008). Our previous research (Dziedzic 2012;Dziedzic et al 2016Dziedzic et al , 2017, as well as the current study, indicate that vigorous rootstocks, especially the Mazzard F12.1 clone, significantly affect the level of SSC in cherry fruits.…”
Section: Discussionsupporting
confidence: 54%
“…Likewise, no significant differences between the rootstocks were shown for the trunk thickness or the volume of the crowns of "Kordia" sweet cherry trees. (Wocior, 2008)  Shoot length (cm) and number of leaves/meter of Kalamata cultivar Data presented in table (3) showed that, Picholine rootstocks produced the best shoot length (14.85 & 16.01 cm) respectively, in 2013 and 2014 seasons of the study, and there was no significant differences between the rest of rootstocks in the second season of the study.…”
Section:  Tree Vigor Of Dolce Cultivarmentioning
confidence: 99%